Local Cultural Adaptation to Digital Nomad Presence: Perspective from Canggu’s Local Community - Anjelia Yovanita; Ni Putu Oka Agustini; I Wayan Sukma Winarya Prabawa (Penerbit Goodwood, 2025)
Purpose: Analyze the cultural adaptation process of the local community in Canggu toward the presence of digital nomads based on Young Yun Kim’s Cultural Adaptation Theory.Research Methodology: A qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. Informants were selected using the snowball sampling technique, while data were analyzed through data reduction, data display, and conclusion drawing.Results: During the stress phase, the community faces language barriers, cultural differences, changes to their environment, traffic congestion and a rise in the cost of living. During the adaptation phase, the community improves its English language skills, gains an understanding of cultural differences, and adapts services and economic activities to the needs of digital nomads. During the growth phase, the community gains economic opportunities, enhances its cross-cultural communication skills, and fosters a sense of self-confidence and pride in Balinese cultural identity. Conclusions: The presence of digital nomads has encouraged a process of adaptation that not only generates economic benefits but also strengthens the cultural identity of the local community. Limitations: Limited to the perspective of the local community in Canggu and therefore does not yet include the views of digital nomads also history and cultural dynamics of Bali have not yet been studied in depth.Contributions: Enriching literature into cultural adaptation in tourist destinations from the perspective of local communities, and to formulate destination management strategies capable of promoting sustainable tourism whilst preserving local cultural identity.